ANALISIS KEPUASAN PELANGGAN TERHADAP PELAYANAN BARBERSHOP DENGAN MENGGUNAKAN METODE SERVICE QUALITY DAN QUALITY FUNCTION DEPLOYMENT - Akhmad Ferdy Firmansyah; Elly Ismiyah; Moh. Jufriyanto (JURNAL REKAYASA SISTEM INDUSTRI, 2021)
For companies in the service sector, especially REF Barbershop, quality improvement and service processes must be customer oriented. To improve the quality of customer service at REF Barbershop, a service quality analysis method is needed. An effective service quality analysis method is to combine the Service Quality (SERVQUAL) method which is integrated with the Quality Function Deployment (QFD) method using the House Of Quality Model. The application of the SERVQUAL method to identify strengths or advantages in the service industry, while the QFD method guarantees that services will be provided according to customer needs. The QFD method using the House Of Quality Model is a collection of matrices containing customer desires and service quality characteristics which are all generated from questionnaire processing. Service design at REF Barbershop using the Service Quality method found a gap that occurred on the customer side, namely between the level of perception and the level of expectation, namely: Availability of toilets obtained a gap value of -0.880, Having good and modern equipment obtained a gap value of -0.580, Cleanliness and completeness equipment, the gap value is -0.360, Availability of queue numbers is obtained the gap value is -0.180, Employees receive consumer complaints quickly, the gap value is -0.140, friendly and courteous service to customers is obtained, the gap value is -0.080. The use of Quality Function Deployment which makes the level of customer satisfaction as the Voice of the Customer and makes the House of Quality then gets 4 Technical Responses, namely: providing training to improve employee performance and rewarding employees whose performance has increased and giving sanctions to employees who perform poorly, providing queue numbers and toilets to increase comfort, improve and schedule regular equipment quality checks, make picket schedules for facility maintenance and cleanliness. From the results of the technical response it can be useful to build and improve services at REF Barbershop.